معالجة المياه المستعملة باستعمال النباتات الصحراوية - عبد الفتاح, رمضاني; نادية, بن عدي (University of El-Oued, 2020)
"قمنا في هذا البحث البسيط بالتعرف على طريقة التصفية المياه المستعملة الملوثة باستخدام النباتات وأهم العوامل التي يجب توفرها لأجل تقديم أفضل تصفية, وهذه الطرقة تسمى أيضا بالمناطق الرطبة. ولهذه الطريقة إيجابيات عدة أهمها عدم التكلفة وعدم استخدام يد عاملة كبيرة وتكون خاصة في المناطق الريفية. وفي الأخير تحقق هذه التقنية استخلاص 85% من الماء المعالج, ويفقد 15% بالتبخر الجوي، وإلى ذلك تمتد بقعة خضراء تثبت التربة وتمنع العواصف الرملية, وتلطف الجو, وهذه التقنية في معالجة الحمأة الصرف الصحي باستخدام الحمأة كأسمدة عضوية مأمونة تغني عن الأسمدة الصناعية. " "In this simple research, we identified a method of filtering contaminated wastewater using plants and the most important factors that must be available in order to provide the best filtration, and this method is also called wet areas. This method has several advantages, the most important of which is the lack of cost and the lack of large labor force, especially in rural areas. In the end, this technique achieves the extraction of 85% of the treated water, and 15% is lost by atmospheric evaporation, and to that extend a green spot that stabilizes the soil and prevents sandstorms, and softens the air, and this technique in treating sewage sludge using sludge as a safe organic fertilizer replaces industrial fertilizers."
Génie chimiqueمذكرة ماستر تخصص
Keywords: المياه المستعملة، النباتات الصحراوية; Wastewater, desert plants